Why is Populism Persuasive? Populism as Expression of Religio-Cultural History with the U.S. and U.S. Evangelicals as a Case Study. Issue 5 (3rd July 2020) - Pally, Marcia
ABSTRACT: Populism is often criticized as a dark political theology as inscrutable as a religion to which one doesn't belong – a messianic craze incompatible with rational government. This article suggests that populisms, left and right, draw from the very historico-cultural background that grounds the societies in which they occur. They are not in revolt against this background but of it. Being grounded in this longstanding background and its cultural repetition, Judith Butler notes, gives populism appeal – what makes it "feel right" and sound true to its audience. In a case study of American populism, including the role of evangelicals, I make a three-part argument. Beginning with a rubric allowing us to identify a movement as populist, I look at (i) religion's contribution to America's historico-cultural background, (ii) how that background funds understandings of society and government, (iii) how these understandings play out in populisms on the left, right, and among evangelicals.